Chinese Calligraphy According to Yinyang Philosophy View, Taoism, and Health Benefits - Dini Khairia (Bambuti, 2022)
In this article I will discuss the meaning of Chinese calligraphy (shufa) based on the views of yinyang philosophy and Taoism in health. This study uses a qualitative method based on literature study, observation, and interviews. The result of this study can be concluded that, in the structure of Chinese calligraphy (shufa) there are elements that make up Chinese calligraphy style continues to develop over time. At this time Chinese calligraphy styles that are widely used by Chinese calligraphy artists are kaishu calligraphy style, caoshu calligraphy style), Zhuanshu篆书 calligraphy style,行书（xingshu）calligraphy style, and古文 (guwen) calligraphy style. In addition to Chinese calligraphy is considered a visual art in writing Chinese calligraphy is also influenced by the views of yinyang philosophy and Taoism as well as in health.